Improvement of Metabolic Parameters Resulted from Levothyroxine Therapy in Hypothyroid Type 2 Diabetes Mellitus Patient - Dante S Harbuwono; Laurentius A Pramono; Hari Hendarto; Imam Subekti (Interna Publishing, 2016)
This is a case of 51 year-old woman with uncontrolled type 2 diabetes mellitus which was diagnosed 1.5 year earlier, obesity with body mass index 32.2 kg/m2, waist circumference of 113 cm, diffuse goiter with neck circumference 40 cm, and hypertension with blood pressure >140/90 mmHg. Since 6 months ago, she often seemed like having less concentration or daydreaming, chronic fatigue, depression, and low food intake. Her body weight had been increasing over time. Her hypothyroidism clinical scoring Billewicz and Zulewski criterias were 17 and 8 respectively, showing that she tended to experience hypothyroidism. From laboratory examination, fasting blood glucose was 216 mg/dL and 2-hour postprandial blood glucose was 320 mg/dL with level of HbA1c was 9.9%, triglyceride level was 486 mg/dL, HDL cholesterol 46 mg/dL, LDL cholesterol 157 mg/dL, and total cholesterol was 269 mg/dL. Thyroid ultrasound showed a diffuse goiter in both lobes of her thyroid gland.